Public budget System repair Targets Prepared Public Budget - شكارة, موفق عباس (Journal of Economics and Administrative Sciences, 2012)
Require senior management of the state when developing the strategy the general budget to the clarity of the reasons that are based upon the ministries in the preparation of estimates of expenditure for the next year to justify the spending, and in the absence of targets, the ministry or government unit would not be in front, but be guided by the size of expenditure for the last year in addition to the percentage of represented an increase of appropriations required for the next year in light of the fiscal policy of the state, so the requested increase in appropriations to meet the desired increase in some of its activities and to meet the increase in salaries and prices. So must be available to the Ministry of criteria that could be relied upon to determine the estimated increase in spending as a result of the projected increase in some activities.It is clear from this that the budget is the outcome of the economic studies of past and under which approval of long-term plan in the light of national objectives needs to be done by the ministries and mean that the budget estimates are derived from data flow from the higher managerial levels and in contrast to the traditional method where the starting estimate budget levels administrative world, then ascend to the levels of the Supreme Administrative Moreover, the programming goals made the programs a central part of the assessment and trade-offs and decision-making regardless of the management levels that are interested in the implementation of the program has been created this way the opportunity to connect the inputs (costs) and outputs (achievements or benefits) for each the program.Supports the proposed model for this system in achieving the goals of government programs to link the state and assess their contribution to the level of macroeconomic and social components of a number of basic requirements which are marginal to the success of this system. And summed up the basic components of this system as follows:• Formulation of goals and sub-quantitatively and qualitatively and temporally. 2. Responsibilities for planning and Implementation and taking control. 3. Develop standard benchmarks to achieve goals.• Calendar periodic performance.